Learning from 'Scrap' about Late Bronze Age Hoarding Practices: A Biographical Approach to Individual Acts of Dedication in Large Metal Hoards of the Carpathian Basin. (21st July 2014) - Dietrich, Oliver
<x content-type="archive" xml:space="preserve">Abstract</x> Hoard finds appear throughout the European Bronze Age with distinct chronological and chorological peaks. While there is some consensus on seeing hoards as an expression of cultic behaviour, the large 'scrap metal' hoards in particular still provoke interpretations as raw material collected for recycling. With socketed axes whose sockets were intentionally filled with deliberately fragmented metalwork, Hansen (1996–1998) has pointed out a group of finds that could be crucial to a better understanding of 'scrap' hoards. Using the finds from the Carpathian Basin as a case study, a dual biographical approach is applied to this group. A close look at the complex use-life of the objects themselves, as well as an attempt at re-integrating them into the local history of hoarding, leads to the conclusion that they constitute single acts of dedication in larger contexts. 'Scrap hoards' can thus be understood as long-term accumulations of votive objects and can be integrated into the social practice of Bronze Age hoarding.